Porcine placenta extract improves high-glucose-induced angiogenesis impairment - Chatchai Nensat; Worawat Songjang; Rutaiwan Tohtong; Tuangporn Suthiphongchai; Suchada Phimsen; Panthip Rattanasinganchan; Pornphimon Metheenukul; Sarawut Kumphune; Arunya Jiraviriyakul (BMC, 2021)
Abstract Background High glucose (HG)-induced reactive oxygen species (ROS) overproduction impairs angiogenesis that is one pivotal factor of wound healing process. Angiogenesis impairment induces delayed wound healing, whereby it eventually leads to amputation in cases of poorly controlled diabetes with diabetic ulceration. Porcine placenta extract (PPE) is a natural waste product that comprises plenty of bioactive agents including growth factors and antioxidants. It was reported as an effective compound that prevents ROS generation. The goal of this study was to investigate the in vitro effect of PPE on HG-induced ROS-mediated angiogenesis impairment. Methods Primary endothelial cells (HUVECs) and endothelial cell line (EA.hy926) were treated with HG in the presence of PPE. The endothelial cells (ECs) viability, intracellular ROS generation, migration, and angiogenesis were determined by MTT assay, DCFDA reagent, wound healing assay, and tube formation assay, respectively. Additionally, the molecular mechanism of PPE on HG-induced angiogenesis impairment was investigated by Western blot. The angiogenic growth factor secretion was also investigated by the sandwich ELISA technique. Results HG in the presence of PPE significantly decreased intracellular ROS overproduction compared to HG alone. HG in the presence of PPE significantly increased ECs viability, migration, and angiogenesis compared to HG alone by showing recovery of PI3K/Akt/ERK1/2 activation. HG in the presence of PPE also decreased ECs apoptosis compared to HG alone by decreasing p53/Bax/cleaved caspase 9/cleaved caspase 3 levels and increasing Bcl 2 level. Conclusion PPE attenuated HG-induced intracellular ROS overproduction that improved ECs viability, proliferation, migration, and angiogenesis by showing recovery of PI3K/Akt/ERK1/2 activation and inhibition of ECs apoptosis. This study suggests PPE ameliorated HG-induced ROS-mediated angiogenesis impairment, whereby it potentially provides an alternative treatment for diabetic wounds.